Normalizing extreme imprisonment: the case of life without parole in California - Vannier, Marion (Clarendon Studies in Criminology, 2021)
Normalizing Extreme Imprisonment offers a new explanation for how penal reforms and those driving them can end up normalizing, in the sense of making the public view as acceptable, incredibly severe punitive practices. Since its introduction in 1978 as an alternative to the death penalty, there has been a dramatic increase and expansion of life without parole (LWOP) in the United States, including beyond the scope of capital crimes for which it was originally conceived. Despite this growth, limited attention has been given to this punishment and very few attempts made to narrow its scope or curtail its proliferation. Emerging scholarship suggests the punishment has been ‘normalized’, in part because of how some death penalty abolitionists have framed and used LWOP. Drawing upon a range of evidence and using the development of LWOP in the Californian death penalty context over 40 years as an example, this book significantly deepens and extends this claim to offer a new explanation for how extreme forms of imprisonment become normalized. To discuss the extent to which some opponents to the death penalty may have facilitated, participated in, or perhaps even animated the three main normalizing mechanisms (visibility, denial, and routinization), this book focuses on three sites where death penalty abolitionists have lobbied, campaigned, pled and settled, for LWOP, namely Congress, the broader political sphere, and courtrooms. The book then contrasts these representations of LWOP’s severity with prisoners’ lived experiences detailed in an exceptional set of 299 letters.